Post-traumatic stress disorder, stress burden, and quality of life among caregivers of children with cancer in Egypt - Ramy, Hisham A.; Sultan, Sara M.; Salama, Rasha A. (Narra Sains Indonesia, 2025)
Caregivers of children with cancer frequently endure considerable psychological distress. The challenging nature of caregiving, combined with the emotional burden of witnessing a child's illness and treatment, can impact the quality of life and lead to the development of post-traumatic stress disorder (PTSD) in these caregivers. The aim of this study was to assess the prevalence of PTSD among caregivers of pediatric cancer patients and to identify the risk factors contributing to its development. Additionally, it examined the stress burden on caregivers and its impact on their quality of life. A cross-sectional comparative study was conducted over six months at the outpatient pediatric oncology clinics in Ain Shams University Hospital and the National Cancer Institute, Cairo, Egypt. The Post-Traumatic Stress Disorder Checklist for DSM-5, Zarit Burden Interview, and PCASEE quality of life were utilized to assess the PTSD symptoms, perceived burden, and quality of life, respectively. A total of 60 caregivers of children with cancer and 60 caregivers of children without cancer were included. Among the caregivers of children with cancer, 91.3% (n=55) exhibited post-traumatic stress symptoms, with 31.3% (n=19) meeting the diagnostic criteria for PTSD, compared to 0% of caregivers of children without cancer. Caregivers of children with cancer had significantly higher stress burden and lower quality of life scores compared to caregivers of children without cancer (48.66±9.95 vs 13.25±5.64; p=0.001 and 51.8±15.2 vs 72.2±14.3; p<0.001, respectively). Young age (p=0.033), being a mother (p=0.003), and taking care of those with tumor relapse (p=0.012) were identified as significant factors associated with PTSD development among caregivers of cancer patients. Moreover, caregivers of children with cancer experienced significantly higher stress burden levels and reduced quality of life compared to those caring for children without cancer (p=0.001), further increasing their risk of developing PTSD. These findings highlight the critical need for targeted psychological support and interventions to improve the well-being of these caregivers.